Challanges in Implementing Activity-Based Costing in Family Businesses: A Case Study of CV PXB - Paramita, Lariza Putri; Violita, Evony Silvino (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p15, 2025)
This study examines the challenges in implementing the Activity-Based Costing (ABC) method at CV PXB, a family-owned company operating in the balsa wood processing industry. As a medium to large-scale enterprise, CV PXB faces various obstacles in transitioning from the traditional costing method to the ABC method. The previously used traditional costing system was deemed inaccurate in allocating overhead costs, thus affecting pricing accuracy and profitability. Data used in this study includes primary data from semi-structured interviews with CV PXB’s management and secondary data from supporting documents. The findings indicate that the main challenges in adopting the ABC method include limited human resources, resistance to change, and the need for training and time investment. However, management’s awareness of ABC’s benefits provides a positive foundation for future implementation. This study aims to offer insights for other family-owned businesses seeking to adopt more modern costing methods. Keywords: activity-based costing; implementation challenges; family businesses